2022
DOI: 10.1158/1538-7445.sabcs21-ot1-04-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT1-04-01: ATNEC: A multi-centre, randomised trial investigating whether axillary treatment can be avoided in T1-3N1M0 breast cancer patients with no residual cancer in the lymph glands after neoadjuvant chemotherapy (clinicaltrials.gov: nct04109079)

Abstract: Background: For patients who are node positive to start at presentation and are found to have a complete nodal tumour response (ypN0) post neoadjuvant chemotherapy (NACT), we do not yet know whether local axillary therapy can be modified based on the response to NACT. ATNEC randomised trial specifically address axillary management following NACT in patients with proven axillary node metastases. Methods: Design: ATNEC is a phase III, randomised (1:1), multi-centre trial, with embedded economic evaluation. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…No difference in other oncologic outcomes was seen, supporting the omission of ALND with either technique. It will be of the utmost interest to see whether the two ongoing prospective randomized trials investigating the omission of ALND and/or nodal irradiation in patients with complete nodal response will confirm these results [120,121]. In the NRG oncology/NSABP B-51/RTOG 1304 trial, which was presented at San Antonio Breast Cancer Symposium (SABCS) 2023, patients who were found node-negative through SLNB and/or ALND after NACT were randomized 1:1 to undergo RNI or not.…”
Section: Patients With Clinically Node-positive Breast Cancer Who Are...mentioning
confidence: 98%
“…No difference in other oncologic outcomes was seen, supporting the omission of ALND with either technique. It will be of the utmost interest to see whether the two ongoing prospective randomized trials investigating the omission of ALND and/or nodal irradiation in patients with complete nodal response will confirm these results [120,121]. In the NRG oncology/NSABP B-51/RTOG 1304 trial, which was presented at San Antonio Breast Cancer Symposium (SABCS) 2023, patients who were found node-negative through SLNB and/or ALND after NACT were randomized 1:1 to undergo RNI or not.…”
Section: Patients With Clinically Node-positive Breast Cancer Who Are...mentioning
confidence: 98%
“…These patients are randomized to receive either whole-breast irradiation (WBI), WBI and RNI after BCS, chest wall irradiation and RNI after mastectomy or no adjuvant radiotherapy (NCT01872975) [ 42 , 43 ]. Furthermore, the UK based ATNEC trial investigates, whether in patients with cT1-3 breast cancer and confirmed nodal-disease pre-NST, who convert to ypN0 confirmed by SLNB after NST, omission of axillary treatment is non-inferior to the control arm receiving either ALND or ART [ 44 ]. However, how to proceed in patients without nodal pCR or in the upfront surgical setting as e.g., in luminal breast cancers representing the majority of breast cancer with low pCR rates when using NST remains an open matter.…”
Section: Axillary Surgery After Neoadjuvant Treatment and Pathologic ...mentioning
confidence: 99%